Transformacja kosmosu w literaturze międzytestamentalnej - Parchem, Marek (2017)
W literaturze międzytestamentalnej, zwłaszcza w pismach o charakterze apokaliptycznym, pojawia się motyw transformacji kosmosu, który stanowi ostatni etap wydarzeń eschatologicznych. Świat skażony grzechem i zdominowany przez siły zła zostanie w czasach ostatecznych przemieniony i odnowiony przez Boga w rzeczywistość doskonałą, gdzie na wieki panować będzie sprawiedliwość i dobro. W niniejszym opracowaniu zostanie omówiona koncepcja transformacji kosmosu, która pojawia się w różnych dokumentach należących do literatury międzytestamentalnej, mianowicie w dziełach egzegetycznych, gdzie pojawiają się również elementy apokaliptyczne (Księga Jubileuszów: Jub 1,29; 4,26; Księdze starożytności biblijnych Pseudo-Filona: LAB 3,10), w zwojach z Qumran (Reguła zrzeszenia: 1QS 4,25) oraz w apokalipsach (Księga astronomiczna: 1 Hen 72,1; Apokalipsa tygodni: 1 Hen 91,14-17; Apokalipsa zwierząt: 1 Hen 90,37-38; Księga przypowieści: 1 Hen 45,4-5; Czwarta Księga Ezdrasza: 4 Ezd 7,28-31.75.113-114; Apokalipsa Barucha syryjska: 2 Bar 32,1-6; 57,1-3).
In the intertestamental literature, especially from various writings of an apocalyptic nature, a recurring motif emerges of the transformation of the universe as the final phase of eschatological events. In the last days, the world – being infected with sin and dominated by the powers of evil – will be renewed and transformed by God into a perfect reality wherein justice and goodness will prevail. In the present article, this notion of the transformation of the universe is explored and discussed. The idea appears in various documents of the intertestamental literature, namely, certain exegetical works such as The Book of Jubilees (Jub 1:29; 4:26) and Biblical Antiquities of Pseudo-Philo (LAB 3:10); the Qumran Rule of the Community (1QS 4:25); and several apocalypses: The Book of Heavenly Luminaries (1 Enoch 72:1), The Apocalypse of Weeks (1 Enoch 91:14-17), The Animal Apocalypse (1 Enoch 90:37-38), The Book of the Similitudes (1 Enoch 45:4-5), The Fourth Book of Ezra (4 Ezra 7:28-31, 75, 113-114), and The Syriac Apocalypse of Baruch (2 Bar 32:1-6; 57:1-3).
In the intertestamental literature, especially from various writings of an apocalyptic nature, a recurring motif emerges of the transformation of the universe as the final phase of eschatological events. In the last days, the world – being infected with sin and dominated by the powers of evil – will be renewed and transformed by God into a perfect reality wherein justice and goodness will prevail. In the present article, this notion of the transformation of the universe is explored and discussed. The idea appears in various documents of the intertestamental literature, namely, certain exegetical works such as The Book of Jubilees (Jub 1:29; 4:26) and Biblical Antiquities of Pseudo-Philo (LAB 3:10); the Qumran Rule of the Community (1QS 4:25); and several apocalypses: The Book of Heavenly Luminaries (1 Enoch 72:1), The Apocalypse of Weeks (1 Enoch 91:14-17), The Animal Apocalypse (1 Enoch 90:37-38), The Book of the Similitudes (1 Enoch 45:4-5), The Fourth Book of Ezra (4 Ezra 7:28-31, 75, 113-114), and The Syriac Apocalypse of Baruch (2 Bar 32:1-6; 57:1-3).
Keywords: apokaliptyka żydowska; eschatologia; odnowienie świata; transformacja kosmosu; literatura międzytestamentalna